Assessing the effects of two agricultural minimum wage shocks in South Africa - Van der Zee, Kirsten (School of Economics, 2017)
In March of 2003, South Africa's first agricultural minimum wage was implemented. Ten years later, following major strikes and protests among farm workers in theWestern Cape, the prescribed agricultural minimum wage was increased by a considerable 52 percent from R69 per day to R105 per day, significantly more than the usual inflation rate increases. This paper investigates the impacts of these two minimum wage shocks, specifically assessing the labour market response in terms of employment, wages and working conditions, as well as assessing how farmers adjusted their operations in expectation of the minimum wage hike. The findings indicate that the probability of employment as a farm worker decreased in response to both minimum wage shocks, however the disemployment effect was sharper for the introduction of the minimum wage than it was for the 2013 amendment. It is observed that relatively more part-time workers lost their jobs in response to the first shock, resulting in there being almost no part-time workers in the sector by the time the second minimum wage shock occurred. Wages increased significantly in response to both minimum wage shocks, however despite this, violation consistently remained a challenge in the sector. Lastly, the paper finds that employment, wages and contract coverage began adjusting up to two quarters prior to the 2013 legislated increase in the minimum wage, suggesting that there are dynamic responses to minimum wages, and that farmers may make operational decisions in expectation of new legislation.